SEKOLAH RAKYAT DI DUSUN RAPAH OMBO MELALUI KEGIATAN SUPER CAMP - M. Bambang Edi Siswanto; Ratih Asmarani; Muhammad Nuruddin (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2022)
Abstract: This research was carried out on the basis of the awareness of the devotees who were moved by their enthusiasm for the people of the Rapah Ombo hamlet. This activity is a unique activity that has never existed in the village so that residents and children are very enthusiastic about participating in this activity. This activity was carried out in the hamlet of Rapah Ombo which is a partner in this service activity, which is one of the hamlets left behind in Jombang Regency because of the difficulty of road access to Dusun Rapah Ombo. This activity is carried out through the Community Learning method or learning community known as the People's School with a Super Camp approach which is a more familiar designation in the ears of the Rapah Ombo community. The results of this study are community service which has been carried out by 60 participants who were divided into 12 groups, each group of 5 people, each group prepared 1 tent, the participants took part in this activity until the end which was closed in the morning with outbound activities and distribution. gifts as an appreciation for their enthusiasm for participating in this activity. This activity is important to continue because it has made the people of the rapah ombo hamlet go viral because it has changed the civilization that initially studied only indoors, now becomes more enthusiastic because they can learn while playing with a tent as a place for them to take shelter.Keywords: People's School, Super Camp, Rapah OmboAbstrak: Pengabdian ini dilaksanakan atas dasar kesadaran dari pengabdi sebagai pemerhati keilmuan yang tergugah semangatnya kepada masyarakat dusun Rapah Ombo kegiatan ini merupakan kegiatan unik yang belum pernah ada di desa tersebut sehingga warga dan anak -anak sangat antusias mengikuti kegiatan ini. Kegiatan ini di laksanakan di dusun rapah ombo yang merupakan mitra dalam kegiatan pengabdian ini, merupakan salah satu dusun yang tertinggal di Kabupaten Jombang sulitnya akses jalan menuju Dusun Rapah Ombo. Kegiatan ini di lakukan melalui metode learning Community atau masyarakat belajar yag di kenal dengan sebutan Sekolah Rakyat dengan pendekatan Super camp yang merupakan sebutan yang lebih femilier di telinga ,masyarakat rapah ombo. Adapun hasil dari Pengabdian ini adalah Pengabdian masyarakat yang telah di lakukan 60 peserta yang di bagi menjadi 12 kelompok setiap kelompok ada 5 orang yang setiap kelompok di siapkan 1 tenda, para peserta mengikuti kegiatan ini hingga selesai yang pagi nya di tutup dengan kegiatan outbond dan pembagian hadiah sebagai apresiasi atas semangat mereka mengikuti kegiatan ini. Kegiatan ini penting untuk terus diadakan karena menjadikan masyarakat dusun rapah ombo menjadi viral karena mengubah peradaban yang awalnya belajar hanya dalam ruangan sekarang menjadi lebih semangat karena bisa belajar sambil bermain dengan tenda sebagai tempat mereka berteduh.Kata kunci: Sekolah Rakyat, Super Camp, Rapah Ombo